Polypropylene and Graphene Nanocomposites: Effects of Selected 2D-Nanofiller’s Plate Sizes on Fundamental Physicochemical Properties - Sarat Chandra Patra; Sumit Swain; Pragyan Senapati; Himadri Sahu; Rabiranjan Murmu; Harekrushna Sutar (Inventions, 2022)
The authors developed a nanocomposite using polypropylene (PP) and graphene nanoplatelets (GNPs) with a melt mixing method. Virgin PP was filled with three sets of GNPs with a fixed thickness (15 nm) and surface area (50–80 m2/g). The selected H-type GNPs had three different sizes of 5, 15 and 25 µm. The nanocomposites were made by loading GNPs at 1, 2 and 3 wt.%. Mechanical analysis was carried out by performing tensile, flexural and impact strength tests. The crystalline, micro-structural, thermal and dynamic mechanical properties were assessed through XRD, FESEM, PLM, DSC, TGA and DMA tests. It was observed that all three types of GNPs boosted the mechanical strength of the polymer composite. Increasing the nanofiller size decreased the tensile strength and the tensile modulus, increased the flexural strength and flexural modulus, and increased the impact strength. Maximum tensile strength (≈41.18 MPa) resulted for the composite consisting 3 wt.% H5, whereas maximum flexural (≈50.931 MPa) and impact (≈42.88 J/m) strengths were observed for nanocomposite holding 3 wt.% H25. Graphene induced the PP’s crystalline phases and structure. An improvement in thermal stability was seen based on the results of onset degradation (TD) and melting (Tm) temperatures. Graphene increased the crystallization (Tc) temperatures, and acted like a nucleating agent. The experimental analysis indicated that the lateral size of graphene plays an important role for the nanocomposite’s homogeneity. It was noted that the small-sized GNPs improved dispersion and decreased agglomeration. Thus overall, small-sized GNPs are preferable, and increasing the lateral size hardly establishes feasible characteristics in the nanocomposite.